“Lir-ilir”: Potential internalization of Javanese cultural values in BIPA materials through Roland Barthes’ semiotic analysis - Diadara, Nova; Yulianeta, Yulianeta; Cahyani, Isah; Mulyati, Yeti (Universitas Mulawarman, 2026)
This study aims to identify the potential of integrating local culture in BIPA materialss through semiotic analysis of the song “Lir-ilir.” Using qualitative descriptive methods and Roland Barthes’ semiotic analysis, the song lyrics were examined in this study. This study showed that denotatively, the song “Lir-ilir” describes rural life. Connotatively, the song is an invitation to improve attitude. Mythologically, the song shows the integration of social, cultural, and religious aspects. The song “Lir-ilir” has cultural values that can be internalized in BIPA materials by studying vocabulary, listening, singing, reading the meaning, and transforming the song “Lir-ilir.” This study contributes to the potential internationalization of Indonesian language through a culture-based approach. The research novelties of this study lie in analyzing the semiotics contained in the song “Lir-ilir” and identifying its potential in BIPA materials as a process of internationalizing Indonesian language and culture. The results of this analysis and potential identification are part of the process of internationalizing the Indonesian language and culture. BIPA course institutions and teachers can develop this teaching material design to enrich the reference of teaching materials and BIPA learning methods that meet the needs of BIPA learners.